Performance curve generation of an unglazed transpired collector system for a fish and crop solar drier - Biona, Jose Bienvenido Manuel M. (Animo Repository, 2002)
One of the factors that hinder the wide scale adaptation of solar dryers is the cost of the solar collectors. In 1991, a low cost but efficient solar collector was developed. Unglazed transpired collectors (UTCs) since then have gained popularity in building heating applications. Its potential for solar drying applications has also been recognized with the development of large scale systems in Canada and United States. It is now currently being explored for small scale drying application in the Philippines. This study focuses on the development of the UTC system performance curve of a solar dryer to be installed in Palawan which would serve as basis for its design. Heat exchange effectiveness plays a critical role in the validity of these curves. Kutscher [1994] has developed and validated a heat exchange effectiveness model for typical UTC air heating applications having plenum depths between 8 in. to 12 in.. The UTC system for dryer being developed limits the plenum depth to 130 mm.A test rig and solar simulator was designed and fabricated for the verification of the applicability of the heat effectiveness model of Kustcher [1994] for UTC plates having plenum depths less than 130 mm. Heat exchange effectiveness of four plates with varying pitch distances between 10 mm to 25 mm were tested on five plenum with depths between 50 mm to 130 mm. Data gathered showed a strong agreement with the energy balance equations of the test system validating their acceptability. The applicability of Kutscher's heat exchange effectiveness model on plenum depths less than 130 mm and below was tested by fitting it with the experimental data. It produced a coefficient of determination (R2) of 0.606. Although this fit was tested acceptable by the model utility F Test, it was further improved by developing a polynomial regression equation of the experimental and Kutscher model heat exchange of effectiveness ratio and multiplying it with the existing model. A computer program was developed generating the predicted temperature rise and collector efficiency for different hold diameter and pitch distance combinations at face suction velocities between 0.2 to 0.6m/s. Results showed that plenum depths produced negligible effect on effective collector efficiency. The performance curves developed could be used to determine the UTC system design that would satisfy a given set of air temperature and flow rate requirement.